PARACETAMOL DISPOSITION IN YOUNG WOMEN: BOTH PREGNANCY AND TOOLS TO AVOID PREGNANCY MATTER. Issue 1 (14th December 2015) - Allegaert, Karel; Peeters, Mariska Y; Beleyn, Bjorn; Smits, Anne; Kulo, Aida; van Calsteren, Kristel; Deprest, Jan; AJ Knibbe, Catherijne
Abstract : Introduction: In this pooled study, we focused on the population pharmacokinetic profile of intravenous paracetamol metabolism and its covariates in young women, including during pregnancy and postpartum. Methods: Population PK parameters using non-linear mixed effect modelling were estimated in a pooled dataset of plasma and urine PK studies in 69 young women [47 at delivery, 8/47 again 10–15 weeks after delivery (early postpartum), and 7/8 again one year after delivery (late postpartum), 22 healthy female volunteers with or without oral contraceptives]. Results: Population PK parameters were estimated based on 815 plasma samples and 101 urine collections. Compared to healthy female volunteers (reference group) not on oral contraceptives, being at delivery was the most significant covariate for clearance to paracetamol glucuronide (F=2.03), while women in early postpartum had decreased paracetamol glucuronidation clearance (F=0.55). Women on contraceptives showed increased paracetamol glucuronidation clearance (F=1.46). The oestradiol level did not further affected this model. Being at delivery did not prove significant for clearance to paracetamol sulphate, but was higher in pregnant women who delivered preterm (<37 weeks, F=1.34) compared to term delivery and non-pregnant women. Finally, clearance of unchanged paracetamol was dependent on urine flow rate. Conclusions: Compared to healthy female volunteers, the urine paracetamol glucuronidation elimination in young women is affected by pregnancy (higher), early postpartum (lower) or exposure to oral contraceptives (higher). This may be of relevance to predict variability in glucuronidation activity in young women and to predict fetal exposure to paracetamol and its metabolites.